The Articulatory description of Finnish vowels using ultrasound - Reunanen Elisa; Saloranta Antti; Peltola Maija S.; Wrench Alan (Latviešu valodas institūta, 2025)
Speech has mostly been studied using measurements of speech sound acoustics. Frequencies of speech are an indirect measure of articulatory movements, and the description of articulatory has mostly been based on
tactile and visual feedback of tongue and lips. The aim of the present study was to describe the articulatory system of Finnish vowels using ultrasound. Subjects’ speech data was collected during a production task in which subject read aloud pseudowords created according to Finnish phonotactic rules. Articulatory movements of the target vowels in words were analysed using Articulatory Assistant Advanced software. Vowel articulatory system was consistent and there was no great within-subject variation. Anatomical differences cause between-subject variation, but despite that, the vowel articulation form a system in which the articulatory movements of different vowels are in same relation with each other. In addition, we noticed that rounding the lips is not the only articulatory movement differentiating rounded and unrounded front vowels in Finnish.